Professor de inglês e o livro didático : concepções teóricas presentes nas orientações do Manual do professor da coleção “Take over” - Marcasso, Fabiana (Universidade Federal de São Carlos, 2017)
Among too much difficulties which affect the success of English teachers of public schools, this search aimed to analyse the teacher profile developed by the didatic book entitled “Take Over” of the Programa Nacional do Livro Didático (PNLD 2015). Through it we offer the reflection about the relationship between the didatic book and the teacher. For this search the prescriptions of the teacher´s book version of the book “Take Over” were analysed, as well as the teacher´s manual available at the end of the book. Besides, we focused on one of the key concepts of theoretical fundamentation of this material: the concept of contextualization. The analysis considers many aspects, such as: the modalizations, the kind of knowledge the authors of this book believe the modern English teachers have, the theoretic – methodological tendencies of these didatic books. So, this is a bibliographical research.
English teacher didactic material : conceptions present in the guidelines of the Teacher manual of the "Take over" collection
Keywords: Livro didático; Papel do professor; Ensino de língua inglesa; Didatic material; Teacher's role; Teaching english language; CIENCIAS HUMANAS::EDUCACAO